GENETIC RISK FACTORS OF TROMBOPHILIA IN WOMEN OF REPRODUCTIVE AGE RESIDING IN KRASNODAR REGION - A. S. Adamchik; D. I. Panchenko (IRBIS LLC, 2016)
Оur paper presents the study of incidence rate of genetic polymorphism of hemostasis genes and folate cycle in patients with habitual miscarriage, residing in Krasnodar region. The property of reproduction age women with habitual miscarriage in juvenile age (75 patients) was the multigene nature of trombophilia in 76.81% of cases (53 patients) from 69 patients with mutations (92% of total number of studied patients) at low percent of incidence of factor V (Leiden) and factor II (prothrombin) gene mutation. It shows that the management of pregnant women, decision on COCs and HRT administration can't be made with testing of a limited number of the most thoroughly studied genes, considered as unconditional and strict markers of inherited thrombophilia (FV, F II, MTHFR С677Т).